1988
DOI: 10.1210/endo-123-5-2303
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Triiodothyronine Transport and Accumulation in Rat Erythrocytes*

Abstract: The transport of L-T3 was studied in washed rat erythrocytes. L-T3 uptake was temperature sensitive: the initial velocity of uptake at low substrate concentration was 40 times higher at 37 C than at 0C whereas, at equilibrium, the ratio of cell-associated to extracellular L-T3 was about 7 times lower at 37 C than at 0 C. When [125I]L-T3-loaded erythrocytes were diluted into a serum albumin-containing medium, the efflux of L-T3 proceeded at a rate similar to that of influx. A large excess of unlabeled L-T3 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 8 publications
3
23
0
Order By: Relevance
“…The transport of thyroid hormones across the plasma membrane determines the intracellular concentration of these hormones and hence the activation of the nuclear T 3 receptor. The existence of mechanisms regulating the transport of thyroid hormones has been suggested in cerebrocortical neurons (17), astrocytes (18), glial cells (19), hepatocytes (20,21), erythrocytes (22), and skeletal muscle (23). The following are comparisons of the pharmacological characteristics among oatp2, oatp3, and the known native thyroid hormone transporters.…”
Section: Discussionmentioning
confidence: 99%
“…The transport of thyroid hormones across the plasma membrane determines the intracellular concentration of these hormones and hence the activation of the nuclear T 3 receptor. The existence of mechanisms regulating the transport of thyroid hormones has been suggested in cerebrocortical neurons (17), astrocytes (18), glial cells (19), hepatocytes (20,21), erythrocytes (22), and skeletal muscle (23). The following are comparisons of the pharmacological characteristics among oatp2, oatp3, and the known native thyroid hormone transporters.…”
Section: Discussionmentioning
confidence: 99%
“…We have carried out a detailed kinetic characterization of the T 3 transport system in the rat erythrocytes and shown that T 3 , but not T 4 , is transported across the plasma membrane by a stereospecific Na + -independent carrier-mediated process and that T 3 is accumulated by intracellular trapping (21). We have also shown that T 3 transport exhibits typical trarcs-inhibition kinetics (22).…”
mentioning
confidence: 99%
“…Also, T3 is taken up in erythrocytes by a low-affinity (Km in mM range) carrier-mediated mechanism [26][27][28][29][30].…”
Section: Cellular Uptake Of Thyroid Hormonementioning
confidence: 99%
“…Furthermore, uptake of both Trp and T3 is inhibited by treatment of erythrocytes with the Cys-specific reagent N-ethylmaleimide, and the inactivation of Trp transport by N-ethylmaleimide is prevented in the presence of T3 and vice versa. These data strongly suggest that thyroid hormone uptake in red blood cells is importantly mediated by a T-type amino acid transporter, that is, a transporter specific for aromatic amino acids [26][27][28][29][30].…”
Section: Cellular Uptake Of Thyroid Hormonementioning
confidence: 99%